Mandatory immunization: Empirical examination of governance instruments in 28 Global NITAG Network (GNN) countries. (30th September 2020) - MacDonald, N; Harmon, S H E; Faour, D; Graham, J; Steffen, C; Henaff, L; Shendale, S
Abstract: Background: In the Global Vaccine Action Plan 2017 Assessment Report, WHO's SAGE noted need to understand ways in which legislation and regulation are used to advance or undermine immunization. The NITAG Environmental Scan Project sought to address this in a pilot study. Methods: Data was collected via a secure online survey of GNN members (40 countries Sept 2018). Respondents reporting a mandatory element were asked: (1) what vaccinations were required by law; and (2) what population groups were subject to mandates; (3) what grounds, if any, were available for requesting exemptions. Results: 28 (70%) countries responded, representing every WHO region and World Bank income level. While mandatory immunization programs / elements within broader NIPs were relatively common, jurisdictions varied with respect to immunizations required, population groups affected, grounds for exemptions, and penalties for non-compliance. We observed some loose associations with geography and income level. Children were the most common population group subject to mandates at some stage of childhood development (28/28); healthcare workers were second (8/15 (53%)). Sanctions for failure to immunize varied broadly, ranging from no penalty, to loss of access to social services e.g. admission to school, monetary fines, and incarceration. A variance between countries as to how strictly immunization mandates are enforced was noted. Conclusions: A variety of approaches existed ranging from Narrow/Permissive to Broad/ Inclusive in scope with enforcement mapping loosely to this continuum from Loose/Permissive to Tight/Coercive. Jurisdictions with few/no vaccines mandated, and few/no target groups identified, Loose approach is expected; for those closer to Broad approach, Tighter controls expected. Coercive measures may be 'positive' (vaccination as a gateway to public services, with possible work-arounds), or 'negative' (failure to vaccinate = penalties).